2020
DOI: 10.18805/lr-4329
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance of Spotted Pod Borer, Maruca vitrata Fabricius in Early Pigeonpea [Cajanus cajan (L.) Millsp.] and its Management through Farmscaping in Uttar Pradesh

Abstract: Field experiments were carried out in pigeonpea during Kharif 2014 to Kharif 2017 for Maruca vitrata Fabricius management through farmscaping approach with 7 different border crops (5 leguminous crops; 2 non-leguminous crops) and a sole crop. The M. vitrata larval webbing per plant was lowest and per cent decrease in webbing/plant over sole crop was highest in sorghum (2.05 and 60.95) as border crop followed by pearl millet (3.29 and 37.39). The highest mean number of Coccinella septumpunctata per plant (0.77)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
3
5
1
Order By: Relevance
“…The results revealed that the coefficient of determination (R 2 ) was significant with the weather parameters viz., maximum temperature, minimum temperature, relative humidity and rainfall contributed directly towards the larval abundance in flowers and pods to the extent of 39.20 and 44.30 per cent, respectively. Moreover, our findings are consistent with the previous reports of Sujayanand et al (2021). They reported that the weather parameters influenced over M. vitrata larval population by 41% (R 2 = 0.41).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The results revealed that the coefficient of determination (R 2 ) was significant with the weather parameters viz., maximum temperature, minimum temperature, relative humidity and rainfall contributed directly towards the larval abundance in flowers and pods to the extent of 39.20 and 44.30 per cent, respectively. Moreover, our findings are consistent with the previous reports of Sujayanand et al (2021). They reported that the weather parameters influenced over M. vitrata larval population by 41% (R 2 = 0.41).…”
Section: Resultssupporting
confidence: 93%
“…Similarly, rainfall showed a significant influence on the larval abundance in pods (B= -0.26). The results are in contrast with the findings of Sujayanand et al (2021). They conveyed that the correlation coefficient (B= -0.12) observed for relative humidity significantly influenced M. vitrata larval population.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…However, as some of these species are invasive to SSA, they should be used cautiously. Crops such as sorghum used as a border in pigeon pea fields increase the abundance of the predators Coccinella septumpunctata , Cheilomenes sexmaculata, and spiders, with a decrease in M. vitrata populations, which eventually leads to increased pigeon pea yields [ 110 ].…”
Section: The Use Of Biological Control As a Central Focus For Aphis Fabae And Maruca Vitrata Contromentioning
confidence: 99%
“…Insect pests are the major constraints resulting in this low productivity, with about 18 insect pests (Jayasinghe et al, 2015;Khan et al, 2018). Notably, the lepidopterans feeding on the flowers and pods of food legumes cause significant yield losses (Rouf and Sardar, 2011;Sreekanth et al, 2019;Tagger et al, 2019;Sujayanand et al, 2021). Amongst this M. vitrata (Lepidoptera: Crambidae) is a serious legume pest with high damage potential and a wider host range (Jackai 1995;Sharma 1999;Margam et al, 2011;and Periasamy et al, 2015).…”
mentioning
confidence: 99%